2021
DOI: 10.1103/physrevb.104.045406
|View full text |Cite
|
Sign up to set email alerts
|

Atomic manipulation of in-gap states in theβBi2Pdsuperconductor

Abstract: Electronic states in the gap of a superconductor inherit intriguing many-body properties from the superconductor. Here, we create these in-gap states by manipulating Cr atomic chains on the β-Bi 2 Pd superconductor. We find that the topological properties of the in-gap states can greatly vary depending on the crafted spin chain. These systems make an ideal platform for nontrivial topological phases because of the large atom-superconductor interactions and the existence of a large Rashba coupling at the Bi-term… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 52 publications
4
28
0
Order By: Relevance
“…[45], the study of the evolution of the in-gap-band structure with the changing parameter together with the spin polarization is an excellent probe to unravel topological phases. Comparison of the Green's function obtained LDOS with experiments indeed show that Cr spin chains on β-Bi 2 Pd wide-band superconductor can undergo a topological phase transition when the number of atoms increase 27 . There, it is also shown that the staggered magnetic moment gives valuable information as predicted in Ref.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…[45], the study of the evolution of the in-gap-band structure with the changing parameter together with the spin polarization is an excellent probe to unravel topological phases. Comparison of the Green's function obtained LDOS with experiments indeed show that Cr spin chains on β-Bi 2 Pd wide-band superconductor can undergo a topological phase transition when the number of atoms increase 27 . There, it is also shown that the staggered magnetic moment gives valuable information as predicted in Ref.…”
Section: Introductionmentioning
confidence: 68%
“…The characterization of molecular-like in-gap states has been made possible by the scanning tunneling microscope (STM) [22][23][24][25] . As more impurities are added, delocalized states form in ferromagnetic structures such that their lowest eigenergies can cross the chemical potential level of the superconductor as has been found experimentally 26,27 . Thus, the spin chain can lead to closing of the superconducting gap and to a phase transition.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations